Numerical Simulation of the Lightning Swept Stroke: Application to the Results From the NASA Storm Hazards Program - Nathanael A. Jenkins; Carmen Guerra-Garcia (IEEE Access)
Understanding how lightning interacts with aircraft is critical to maintaining air transportation safety. This is increasingly important as the aviation industry moves towards more efficient, less conventional aircraft, for which no historical information on lightning attachment is available. This paper presents a physics-based numerical model for the lightning swept stroke phase that is agnostic to the aircraft geometry and therefore has greater generality than current approaches. The validity of the model is addressed by comparison to flight data from the NASA Storm Hazards Program, which recorded 714 lightning strikes on an F-106B aircraft for flights conducted between 1980 and 1986. The model can handle both inviscid and viscous flows, and can be used to understand the sensitivity of the predictions to the flow field, arc reattachment criteria, and flight conditions. Results using a Reynolds-averaged viscous fluid model affirm the importance of transient, small-scale turbulence to predict reattachment of individual arcs. An inviscid fluid model is seen to be sufficient to determine the probabilistic distribution of strikes on the aircraft. The model correctly highlights regions of high and low lightning-attachment probability. Parametric explorations show that the local electrical breakdown of an air gap is not the primary mechanism leading to reattachment in the inviscid model: arc sweeping, followed by geometrical intersection, is a more likely mechanism. The main contributor to the lightning strike distribution is the aircraft attitude and the results are less sensitive to altitude, air speed, and arc parameters. These results provide a valuable data-point for the validation of a physics-based approach to modeling lightning strikes on aircraft.